Corrosion evaluation of carbon steel bars by magnetic non-destructive method. Issue 3 (4th May 2022) - Diogenes, Aldecira G.; de Moura, Elineudo Pinho; da Silveira Machado, André; Gonçalves, Lindberg Lima
ABSTRACT: Reinforced concrete structures undergo various degradation processes, mainly rebars corrosion. Recently, magnetic non-destructive tests have been used to study the steel components used in concrete structures. This paper proposes a non-destructive method, based on the electromagnetic induction technique, capable of identifying corrosion in steel bars. Therefore, through signals obtained from sinusoidal and triangular waveform excitations, magnetic hysteresis loops were determined in steel bars of 5.0, 6.3, 8.0, 10.0, 12.5 and 16.0 mm diameters at 0, 10 and 20 mm depths. Magnetic tests were performed in uncorroded steel bars and in bars that have been exposed to corrosion by the salt spray test. The magnetic responses, remanence, coercivity and the maximum values of hysteresis curves obtained were organised into classes for uncorroded and corroded bars of each steel diameter, totalling 12 classes. A statistical analysis of the experimental results has been performed, and a detailed analysis of the data has also been performed by using the pattern classification techniques, namely, principal component analysis, Karhunen–Loéve transformation, Gaussian classifier and artificial neural network. The results show that the investigated method has great potential of becoming an electromagnetic non-destructive technique for the identification of corroded steel bars in concrete structures.